2011
DOI: 10.1103/physreva.84.063616
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size and particle-number effects in an ultracold Fermi gas at unitarity

Abstract: We investigate an ultracold Fermi gas at unitarity confined in a periodic box V = L 3 using renormalization group (RG) techniques. Within this approach we can quantitatively assess the long range bosonic order parameter fluctuations which dominate finite-size effects. We determine the finite-size and particle-number dependence of universal quantities, such as the Bertsch parameter and the fermion gap. Moreover, we analyze how these universal observables respond to the variation of an external pairing source. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…The FRG approach has been applied to study the effect of compactified dimensions on many-body system both in several relativistic and non-relativistic setups. Finite volume effects, i.e., when all spatial directions are confined to a cube of size [0, L] d , have been studied for quarkmeson-models [46][47][48][49] and the 3D BCS-BEC crossover [50]. In particular, Ref.…”
Section: Modelmentioning
confidence: 99%
“…The FRG approach has been applied to study the effect of compactified dimensions on many-body system both in several relativistic and non-relativistic setups. Finite volume effects, i.e., when all spatial directions are confined to a cube of size [0, L] d , have been studied for quarkmeson-models [46][47][48][49] and the 3D BCS-BEC crossover [50]. In particular, Ref.…”
Section: Modelmentioning
confidence: 99%
“…However, we have checked that the results remain qualitatively unchanged even if we include corrections arising from such fluctuations [42]. We stress that we aim at an understanding of the deviation of ξ from its value in the thermodynamic limit.…”
Section: Fermi Gas In a Finite Boxmentioning
confidence: 94%
“…Note that the particle number is determined by the quantity k F L, where k F is the Fermi momentum. For details, we refer the reader to see [42] (color figure online) a spontaneous breakdown of the U(1) symmetry of the theory. In the following we will not give all the details of our finite-volume study which can be found in [42].…”
Section: Fermi Gas In a Finite Boxmentioning
confidence: 99%
“…Eq. (13)]. The extension to the larger domain should be done respecting the periodicity of the momentum lattice.…”
Section: Appendix A: Evaluation Of S(η)mentioning
confidence: 99%
“…[10] for the Hubbard model using dynamical mean-field theory, careful systematic studies in full-fledged MC calculations have only recently started to appear [4,5,11,12] and are still restricted to the ground state. Interestingly, recent studies based on functional renormalization group techniques [13] have also started to tackle the problem of extrapolating to infinite volume and particle number in the unitary limit.…”
Section: Introductionmentioning
confidence: 99%